Implementasi TIK Untuk Guru SD Yang Inovatif - Sugiarto, Alvina Arta Amalia; Hasanah, Nur; Mareta, Ervitriana; Endang, Avelina Trinita; Hasanah, Uswatun (PT. Riset Press International, 2024)
In the current of the world of education, techers are required to follow technological developments that are able to make students develop and have character. Teachers can create quality learning media using ICT. One of the actifivities that can increase creative and innovative elementary school teachers is throgh the implementation of ICT, by participating in webinar activities which are carried out via webinars. The aim of this webinar is to form teachers ang prospective teachers to become innovative and creative teachers through the implementation of ICT.